Application of estrus synchronization for artificial insemination to improve productivity and quality of beef cattle - Thu, Do Van; Binh, Doan Viet; Ty, Le Van; Hue, Le Thi; Khoi, Tran Dang (Academia Journal of Biology, 2013)
Local yellow cattle breed still made up a high percentage of total cattle population in Vietnam. These breed should be inseminated with exotic breed to increase their genetic merit. As the cattle bred in smallholder farmers display estrus sporadic and unconcentrated, application of artificial insemination (AI) tends to limit to areas in close proximity to urban city. Therefore, solutions should be found to enhance the possibilities for using artificial insemination. This paper reports the application of estrus synchronization for artificial insemination of beef cattle. A total of 524 local yellow and Sind crossbreed cattle were assigned randomly into one of two experimental groups. Group 1: cows received 2 ml of PGF2α, followed in 11 d with 2 ml PGF2α and 500 UI PMSG on the same day. Group 2: cows were administered 100 µg GnRH, followed in 7 d with 2 ml of PGF2α. After the last injection in each group, cows were observed for estrus twice daily and those displaying estrus were artificial inseminated. At the end of experiment, rates of detected estrus, conception and parturition in the group 1 and 2 are 84.90 and 82.08%, 82.88 and 80.28%, 93.52 and 92.98% respectively. The results showed that synchronization of estrus has the potential to enhance the possibilities for using AI and help to improve productivity and quality of beef cattle.